Fractional Derivatives with Mittag-Leffler Kernel Trends and Applications in Science and Engineering - Gómez, José Francisco; Torres, Lizeth; Escobar, Ricardo Fabricio (Studies in Systems, Decision and Control,, 2019)
This book offers a timely overview of fractional calculus applications, with a special emphasis on fractional derivatives with Mittag-Leffler kernel. The different contributions, written by applied mathematicians, physicists and engineers, offers a snapshot of recent research in the field, highlighting the current methodological frameworks together with applications in different fields of science and engineering, such as chemistry, mechanics, epidemiology and more. It is intended as a timely guide and source of inspiration for graduate students and researchers in the above-mentioned areas.